2007
DOI: 10.1682/jrrd.2006.08.0101
|View full text |Cite
|
Sign up to set email alerts
|

Bridging science to service: Using Rehabilitation Research and Training Center program to ensure that research-based knowledge makes a difference

Abstract: Abstract-The challenge of bridging science to service is increasingly visible in the healthcare field, with emphasis on the influence of evidence-based knowledge on both policy and practice. Since its inception more than 40 years ago, the Rehabilitation Research and Training Center (RRTC) program has provided grants for both research and training activities designed to ensure that research knowledge is translated into practice. The RRTC program is unique in that its mission and funding have always required tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 74 publications
(105 reference statements)
0
27
0
1
Order By: Relevance
“…29,30 Another barrier that has been described in the literature is the inability of clinicians to apply research to patients seen in practice. 5,10,13,21,31,32 It has been reported that clinicians perceive a significant barrier in applying research findings from a group of subjects to an individual patient with specific characteristics since research implications for practice in the original research report may not be stated clearly. 10,13 According to Grimmer-Somers et al 10 , physical therapists feel that research results may not be applicable to their particular setting.…”
Section: Factors Affecting Ke and Ktmentioning
confidence: 99%
See 1 more Smart Citation
“…29,30 Another barrier that has been described in the literature is the inability of clinicians to apply research to patients seen in practice. 5,10,13,21,31,32 It has been reported that clinicians perceive a significant barrier in applying research findings from a group of subjects to an individual patient with specific characteristics since research implications for practice in the original research report may not be stated clearly. 10,13 According to Grimmer-Somers et al 10 , physical therapists feel that research results may not be applicable to their particular setting.…”
Section: Factors Affecting Ke and Ktmentioning
confidence: 99%
“…1,2 Transfering scientific evidence to clinicians has been identified as a challenge among rehabilitation professions and a gap between the scientific evidence and its application in clinical practice has been described. [3][4][5] The failure to translate scientific evidence into clinical practice contributes to the gap between what is known and what is done, leading to the underuse of efficacious treatments, erroneous use of treatments and overuse of inefficacious or unevaluated treatments. 1,6 The identification of this gap has led to the development of a special interest and further investigation in KE and knowledge translation (KT).…”
Section: Introductionmentioning
confidence: 99%
“…While the enviable economic context of this arrangement is unusual it is not unique (Farkas and Anthony, 2007) and it could be reproduced elsewhere. Nevertheless, the regular presentation of research findings directly to knowledge users is a common strategy for influencing decision makers (Bogenschneider et al, 2000), and we have demonstrated that its success can be measured.…”
Section: Discussionmentioning
confidence: 99%
“…The speaker series served as an exposure strategy that had an impact on staff attitudes and knowledge, which is the first step toward substantively changing practice. It also demonstrated that skills and implementation cannot be derived through exposure alone, and a more substantive investment is needed to fundamentally change the way that inpatient care is provided (31,32). To effectively have an impact on practice, this training would likely need to be considered as a component of a larger intervention that would more explicitly address skill development through mentorship and organizational structures that embed new practices as routine care (32).…”
Section: Discussionmentioning
confidence: 99%